Hubungan Partisipasi Ke Posyandu Dengan Kenaikan Berat Badan Balita Di Desa Wonorejo, Kemasan, Bugel Kecamatan Polokarto Sukoharjo - Dyna Muharam, Iqbal, Luluk Ria Rakhma.,S.Gz., M.Gizi (2016)
Background: Posyandu or Pos Pelayanan Terpadu (Integrated Service Post) becomes essential health service for baby and toddler earliest. However in society, the fact is many people do not take the advantages of Posyandu to monitor their child growth because they are too busy at work as the reason or they do not have time to bring their toddler to Posyandu and lack of knowledge about the importance of child growth monitoring. Objective: The aim of this research is to know the participation relationship to Posyandu towards toddler's weight gain. Research Method: This research is observational with cross sectional approach. Participation data in Posyandu and weight of toddler is taken directly from the records of toddler's healthy card (KMS). Data analysis is using Chi-Square test. Result: There is a relation between participation relationship to Posyandu and weight gain with P value is 0,000. Conclusion: Toddler's mother participation in Posyandu who come routinely is 73 (74.5%) and who does not come routinely is 25 (25.5%) it is seen from the last six months, toddler's weight gains is 42 (42.9%) and toddler's weight losses is 56 (57.1%) it is seen from the last three months, there is a relation between participation relationship to Posyandu and weight gain. Suggestion: This research can be information and recommendation for Puskesmas (Pusat Kesehatan Masyarakat) or Community Health Center at Polokarto in providing guidance participation to Posyandu and give reference to develop further research related with participation to Posyandu towards toddler's weight gain. Key words : Participation to Posyandu, Toddler's weight gain.